Vegetation Structure and Diversity in Northern Yobe, Nigeria (Asian Journal of Plant Biology, 2022)
The study examined the diversity of vegetation (tree species and shrubs) for the preservation, utilization and conservation of tree species in Northern Yobe. A point centred quarter (PCQ) method was employed to study the vegetation structure in six randomly selected experimental sites across the three local government councils in Northern Yobe (Yunusari, Yusufari and Geidam). A total of 22 tree species and 7 shrubs belonging to 15 families were identified, with Fabaceae being the family with the highest number of tree species (5 members), and followed by Combretaceae, Mimosaceae, and Rhamnaceae each with 3 members. Aracaceae, Euphorbiaceae, Rhamnaceae, and Moraceae have 2 members each, while other identified families had a member of tree species. Specifically, Sodom apple was the dominant tree species based on Importance Value Indices (IVI) of 23.3, followed by Doum palm (22.0), then Guiera tree and Combretum species, each with IVI of 20.7, followed by Desert date (20.3), Thorn Acacia (19.9), and then Whistling thorn (19.3 as their IVI. The Diversity index was determined as 1, Simpson’s index of diversity was very low (-0.0082) and the species richness was 0.41. The low values indicate a less complex community, and the distribution pattern of the various parameters assesses was that of a typical Sahel-Savannah vegetation. Nevertheless, there was a large number of different tree species (29) recorded which implies many tree species are adaptable in the study area but only regenerated naturally without effort for intensive production. Therefore, the need of mass production of these trees in plantation and agroforestry for the conservation and utilization of the dominant (most adapted) tree species to halt environmental associated problems including desertification and erosion in the study area.
Keywords: Adaptability; Diversity; Taxonomy; Tree species; Shrubs